Melatonin suppresses platelet activation and function against cardiac ischemia/reperfusion injury via PPARγ/FUNDC1/mitophagy pathways. Issue 4 (21st August 2017) - Zhou, Hao; Li, Dandan; Zhu, Pingjun; Hu, Shunying; Hu, Nan; Ma, Sai; Zhang, Ying; Han, Tianwen; Ren, Jun; Cao, Feng; Chen, Yundai
Abstract: Platelet activation is a major (patho‐) physiological mechanism that underlies ischemia/reperfusion (I/R) injury. In this study, we explored the molecular signals for platelet hyperactivity and investigated the beneficial effects of melatonin on platelet reactivity in response to I/R injury. After reperfusion, peroxisome proliferator‐activated receptor γ (PPARγ) was progressively downregulated in patients with acute myocardial infarction undergoing coronary artery bypass grafting (CABG) surgery and in mice with I/R injury model. Loss of PPARγ was closely associated with FUN14 domain containing 1 (FUNDC1) dephosphorylation and mitophagy activation, leading to increased mitochondrial electron transport chain complex (ETC.) activity, enhanced mitochondrial respiratory function, and elevated ATP production. The improved mitochondrial function strongly contributed to platelet aggregation, spreading, expression of P‐selectin, and final formation of micro‐thromboses, eventually resulting in myocardial dysfunction and microvascular structural destruction. However, melatonin powerfully suppressed platelet activation via restoration of the PPARγ content in platelets, which subsequently blocked FUNDC1‐required mitophagy, mitochondrial energy production, platelet hyperactivity, and cardiac I/R injury. In contrast, genetic ablation of PPARγ in platelet abolished the beneficial effects of melatonin on mitophagy, mitochondrial ATP supply, and platelet activation. Our results lay the foundation for the molecular mechanism of platelet activation in response to I/R injury and highlight that the manipulation of the PPARγ/FUNDC1/mitophagy pathway by melatonin could be a novel strategy for cardioprotection in the setting of cardiac I/R injury.